Explorasi dan Studi Komposisi Botani Gulma di Perkebunan Karet PTPN IX Kebun Getas sebagai Pakan Ternak Ruminansia - Harwanto, Harwanto; Suwignyo, Bambang; Bachruddin, Zaenal; Pawening, Galih (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2021)
Abstract Weed is one of the plants that grow around rubber plantations that have the potential to provide forage for ruminant feed. This study aimed to explore the environmental conditions and identify the botanical composition of weeds under the shade of rubber trees in immature plants (IP) at PTPN IX, Getas Farm, Semarang, Central Java. Exploratory research was conducted to identify the botanical composition of weeds in three IP groups, such as 1-2, 3-4, and 5-6 years old. The composition of the weeds’ botany was divided based on the plants’ morphology into grass, legume, forbs, and browse. The environmental conditions data were analyzed using the ANOVA method and followed by Duncan's Multiple Range Test (DMRT). The botanical composition data were tabulated using a summed dominance ratio (SDR). The results showed the light intensity, wind speed, environment temperature, and weed botanical composition decreased as the rubber plants ages. The composition of rubber plantation weeds on IP 1-2 years old consisted of 32 species (5 kinds of grass, 4 legumes, 21 forbs, and 2 browse). The composition of weeds on IP 3-4 years old consisted of 15 species (8 kinds of grass, 2 legumes, and 5 forbs), while IP 5-6 years old consisted of 6 species (4 kinds of grass, 1 legume, and 1 forb). The dominant weeds of each IP were Calopogonium mucunoides, Cyrtococcum acrescens, and Cyrtococcum oxyphyllum, respectively. Based on the results of the study it was concluded that the area of IP 1-2 years old rubber plantation weeds has the highest botanical composition and potential as ruminant feed. Keywords: Environmental conditions; Immature plants; Rubber plantation; Weed Abstrak Gulma merupakan salah satu tanaman yang tumbuh di sekitar tanaman perkebunan karet yang berpotensi sebagai penyedia hijauan pakan ternak ruminansia. Penelitian ini bertujuan untuk mengeksplorasi kondisi lingkunganpertumbuhan gulma dan mengidentifikasi komposisi botani di bawah naungan pohon karet pada tanaman belum menghasilkan (TBM), di PTPN IX, Kebun Getas. Semarang, Jawa Tengah. Penelitian dilakukan secara eksploratif terhadap kondisi lingkungan dan identifikasi komposisi botani gulma pada 3 kelompok TBM yaitu umur 1-2; 3-4; dan 5-6 tahun. Komposisi botani gulma dibagi berdasarkan morfologi tanaman yaitu rumput, legum, forb, dan browse. Data kondisi lingkungan kelompok TBM dianalisis menggunakan ANOVA dan diuji lanjut menggunakan Duncant’s Multiple Range Test (DMRT). Data dominasi komposisi botani ditabulasi menggunakan summed dominance ratio (SDR). Hasil penelitian menunjukkan intensitas cahaya, kecepatan angin, suhu lingkungan, dan komposisi botani gulma menurun seiring bertambahnya umur tanaman karet. Komposisi gulma perkebunan karet pada TBM 1-2 terdapat 32 spesies meliputi 5 rumput, 4 legum, 21 forb, dan 2 browse; TBM 3-4 terdapat 15 spesies meliputi 8 rumput, 2 legum, dan 5 forb, sedangkan TBM 5-6 terdapat 6 spesies meliputi 4 rumput, 1 legum, dan 1 forb. Gulma yang mendominasi masing-masing TBM yaitu Calopogonium mucunoides, Cyrtococcum acrescens dan Cyrtococcum oxyphyllum. Berdasarkan hasil penelitian disimpulkan gulma perkebunan karet lahan TBM 1–2 memiliki komposisi botani dan potensi tertinggi sebagai pakan ternak ruminansia. Kata kunci: Gulma; Kondisi lingkungan; Perkebunan Karet; TBM